Hospital volume, calendar age, and short term outcomes in patients undergoing repair of abdominal aortic aneurysms: the Ontario experience, 1988-92. Issue 2 (April 1996) - Wen, S W; Simunovic, M; Williams, J I; Johnston, K W; Naylor, C D
Abstract : OBJECTIVE: To determine, for abdominal aortic aneurysm surgery, whether a previously reported relationship between hospital case volume and mortality rate was observed in Ontario hospitals and to assess the potential impact of age on the mortality rate for elective surgery. DESIGN: Population based observational study using administrative data. SETTING: All Ontario hospitals where repair of abdominal aortic aneurysm as a primary procedure was performed during 1988-92. PATIENTS: These comprised 5492 patients with unruptured abdominal aortic aneurysms and 1203 patients with ruptured abdominal aortic aneurysms admitted to hospital between 1988-92 for repair of abdominal aortic aneurysm as a primary procedure. MAIN OUTCOMES: In-hospital death and length of in-hospital stay. RESULTS: The case fatality rate was 3.8% for unruptured abdominal aortic aneurysms and 40.0% for ruptured abdominal aortic aneurysms. For unruptured cases, after adjustment for patient and hospital covariates, each 10 case per year increase in hospital volume was related to a 6% reduction in relative odds of death (odds ratio (OR) 0.94, 95% confidence intervals 0.88, 0.99) and 0.29 days reduction (95% CI -0.22, -0.35) in postoperative in-hospital stay. Female sex (OR 1.53, 95% CI 1.08, 2.18) and transfer from another acute care hospital (OR 4.37, 95% CI 2.62, 7.29) were associated with increased case fatality rates among patients in the unruptured category. For ruptured cases, neither the case fatality rate nor postoperative in-hospital stay were significantly related to hospital volume. The case fatality rates increased linearly and substantially with advancing age both for unruptured and ruptured aneurysms, and the excess risk of postoperative death in ruptured as compared to unruptured aneurysms was substantially higher in older patients. CONCLUSION: The relationship between hospital volume and mortality or morbidity was very modest and observed only for elective surgery. Case fatality rates in patients with ruptured abdominal aortic aneurysms remained 10 times higher than for patients with unruptured abdominal aortic aneurysms, despite improvements in overall mortality in comparison to previously published data. More effective detection of aneurysms, including elective repair for those once considered "high risk" older patients, might further reduce the toll from ruptured aortic aneurysms.